INCLUSIVE TOURISM READINESS OF TONDOK BAKARU VILLAGE: AN EVIDENCE-BASED ASSESSMENT FOR SUSTAINABLE DEVELOPMENT - Nur Adyla Suriadi; Arifuddin Akil; Amran Achmad (Politeknik Pariwisata Makassar, 2025)
Tondok Bakaru Village is a buffer village that borders Gandang Dewata National Park and is a tourist village that has been ranked among the top 50 in the 2022 ADWI (Awards for the Development of Tourism Villages). The sustainable and inclusive development of tourism in the buffer village of Tondok Bakaru is strategically necessary to maintain a balance between environmental conservation, community empowerment, and local economic growth. Methodologically, this study uses a descriptive quantitative approach with a Likert scale-based scoring analysis technique to measure and assess the level of implementation of inclusive tourism principles in the Tondok Bakaru Tourism Village. Scoring is applied to indicators in five dimensions of inclusivity: physical and environmental accessibility, socio-culture, economy, management and policy, and information and communication technology. The results of this assessment were then processed to determine the tourism village inclusiveness index. A qualitative approach is used in semi-structured interviews/focus groups with key stakeholders (local communities, tourism businesses, tourists, and vulnerable groups) and document review. The scope covers core attractions and supporting services in Tondok Bakaru Village, as well as governance arrangements and local enterprises. The objective is to establish a rigorous baseline for inclusive tourism implementation, identify principal constraints and enablers, and formulate actionable priorities that link inclusion with sustainability. The findings provide actionable evidence for village managers and policymakers to steer investments toward high-leverage improvements and measurable progress toward sustainable destination status.